### What is Recursion?

A recursive function is a function that calls itself until it doesn’t. And this technique is called recursion.

### Syntax

```
const recurse = () => {
recurse();
}
recurse();
```

This recursive function will keep calling itself forever, So it needs a little more touches

```
const recurse = () => {
if (condition) {
recurse();
}
// stop calling recurse()
};
recurse();
```

This function will continue calling itself as it meets the condition, else will stop running.

### Examples

#### 1- Simple Example

```
const countDown = (start, end) => {
console.log(start);
if (start > end) {
countDown(start - 1, end);
}
};
countDown(19, 7); // 19 18 17 16
```

#### Behind the scenes

- countDown(19, 7) prints 19 and calls countDown(18, 7)
- countDown(18, 7) prints 18 and calls countDown(17, 7)
- countDown (17, 7) prints 17 and calls countDown(16, 7)
- countDown (16, 7) prints 16 and stop running.

#### 2- Factorial

- 0! = 1
- 1! = 1
- 2! = 2 * 1
- 3! = 3 * 2 * 1
- 4! = 4 * 3 * 2 * 1
- 5! = 5 * 4 * 3 * 2 * 1

```
const factorial = (num) => (num < 0 ? -1 : num === 0 ? 1 : num * factorial(num - 1));
console.log(factorial(5)); // 120
```

#### Behind the scenes

- factorial(5) = 5 * factorial(4)
- factorial(4) = 4 * factorial(3)
- factorial(3) = 3 * factorial(2)
- factorial(2) = 2 * factorial(1)
- factorial(1) = 1 * factorial(0)
- factorial(0) = 1

#### 3- Fibonacci

A fibonacci sequence is written as:

0, 1, 1, 2, 3, 5, 8, 13, 21, ...

The Fibonacci sequence is the integer sequence where the first two terms are 0 and 1. After that, the next term is defined as the sum of the previous two terms. Hence, the nth term is the sum of (n-1)th term and (n-2)th term.

Here's a code that returns the fibonacci value at a given index using recursion

```
const fibonacci = (n) => (n < 2 ? n : fibonacci(n - 1) + fibonacci(n - 2));
console.log(fibonacci(5)); // 5
```

#### Behind the scenes

- fibonacci(5) = fibonacci(4) + fibonacci(3)
- fibonacci(4) = fibonacci(3) + fibonacci(2)
- fibonacci(3) = fibonacci(2) + fibonacci(1)
- fibonacci(2) = fibonacci(1) + fibonacci(0)
- fibonacci(1) = 1
- fibonacci(0) = 0

## Top comments (0)